2013
DOI: 10.1038/srep02666
|View full text |Cite
|
Sign up to set email alerts
|

Precisely aligned graphene grown on hexagonal boron nitride by catalyst free chemical vapor deposition

Abstract: To grow precisely aligned graphene on h-BN without metal catalyst is extremely important, which allows for intriguing physical properties and devices of graphene/h-BN hetero-structure to be studied in a controllable manner. In this report, such hetero-structures were fabricated and investigated by atomic resolution scanning probe microscopy. Moiré patterns are observed and the sensitivity of moiré interferometry proves that the graphene grains can align precisely with the underlying h-BN lattice within an erro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
189
1
56

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(264 citation statements)
references
References 58 publications
18
189
1
56
Order By: Relevance
“…These dielectric properties of h-BN are comparable with that of SiO 2 making h-BN a promising alternative substrate for graphene with improved high-temperature and high-electric field performance. The latter is due to almost twice larger surface optical phonon frequency of h-BN than similar modes in SiO 2 [4].Moiré patterns are observed in aligned graphene on h-BN. It was found that graphene flakes can align with the underlying h-BN lattice within an error of less than 0.05 o [4,7].…”
mentioning
confidence: 65%
“…These dielectric properties of h-BN are comparable with that of SiO 2 making h-BN a promising alternative substrate for graphene with improved high-temperature and high-electric field performance. The latter is due to almost twice larger surface optical phonon frequency of h-BN than similar modes in SiO 2 [4].Moiré patterns are observed in aligned graphene on h-BN. It was found that graphene flakes can align with the underlying h-BN lattice within an error of less than 0.05 o [4,7].…”
mentioning
confidence: 65%
“…The B-N bond length is close to that of C-C with only a very small (1.6%-2%) lattice mismatch [4,5] which results in the appearance of a Moiré pattern (MP) when GE is put on top of BN. It was found that GE flakes can align with the underlying h-BN lattice within an error of less than 0.05 o [4,6]. Ab-initio and semi-empirical van der Waals studies showed that the interaction between GE flakes and the h-BN substrate is similar to that of a GE-GE stacked structure [7].…”
mentioning
confidence: 99%
“…For example, hexagonal boron nitride has turned out to be an ideal dielectric substrate which is atomically flat and improves graphene's mobility by more than two orders of magnitude [2,3]. The B-N bond length is close to that of C-C with only a very small (1.6%-2%) lattice mismatch [4,5] which results in the appearance of a Moiré pattern (MP) when GE is put on top of BN. It was found that GE flakes can align with the underlying h-BN lattice within an error of less than 0.05 o [4,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…- 15 and experimentally. [16][17][18][19][20] The earliest experiments on different samples showed conflicting results on the existence of an insulating state at the neutrality point. Some experiments 21 suggested the existence of an electronic gap of about ∼ 30 meV, while others do not see any clear evidence of it.…”
Section: Introductionmentioning
confidence: 99%